Cholesterol Is a Dose-Dependent Positive Allosteric Modulator of CCR3 Ligand Affinity and G Protein Coupling - van Aalst, Evan; Wylie, Benjamin J. (Frontiers in Molecular Biosciences, 2021)
Cholesterol as an allosteric modulator of G protein-coupled Receptor (GPCR) function is well documented. This quintessential mammalian lipid facilitates receptor-ligand interactions and multimerization states. Functionally, this introduces a complicated mechanism for homeostatic modulation of GPCR signaling. Chemokine receptors are class A GPCRs responsible for immune cell trafficking through binding of endogenous peptide ligands. CCR3 is a CC motif chemokine receptor expressed by eosinophils and basophils. It traffics these cells by transducing signal stimulated by the CC motif chemokine primary messengers 11, 24, and 26. These behaviors are intimate to human immunoresponse. Thus, CCR3 is implicated in cancer metastasis and inflammatory conditions. However, there is a paucity of experimental evidence linking the functional states of CCR3 to the molecular mechanisms of cholesterol-receptor cooperativity. In this vein, we present a means to combine codon harmonization and a Maltose Binding Protein fusion tag to produce CCR3 from E. coli. This technique yields ~2.6 mg of functional GPCR per liter of minimal media. We leveraged this protein production capability to investigate the effects of cholesterol on CCR3 function in vitro. We found that affinity for the endogenous ligand CCL11 increases in a dose-dependent manner with cholesterol concentration in both Styrene:Maleic acid lipid particles (SMALPs) and proteoliposomes. This heightened receptor activation directly translates to increased signal transduction as measured by GTPase activity of the bound G-protein  inhibitory subunit 3 (Gαi3). This work represents a critical step forward in understanding the role of cholesterol-GPCR allostery in regulation of signal transduction.